Effect of potassium nitrate plus vitamin C in feed of rabbits on the some biochemical parameters - Jassim Alrawi, Saad Thabit (The Iraqi Journal of Veterinary Medicine, 2017)
This study is conducted at investigating the effect of potassium nitrate and vitamin C in feed of the rabbits on the some biochemical parameters. Twenty eight adult New-Zealand rabbits were divided randomly into four groups (7 rabbits each), they were fed potassium nitrate and vitamin C for 16 weeks as follow: Group 1 (G1) fed potassium nitrate (168 mg/ kg B.W./ daily), group 2 (G2) fed potassium nitrate (168 mg/ kg B.W./ daily) and vitamin C (50 mg/ kg B.W./ daily), group 3 (G3) fed potassium nitrate (168 mg/ kg B.W./ daily) and vitamin C (100 mg/ kg B.W./ daily) and group 4 (G4) fed basal ration as control group. Blood were collected from heart at zero, eight, twelve and sixteen weeks. The results showed a significant increase (P<0.05) in cholesterol, triglyceride and blood nitrogen urea in the group that had fed potassium nitrate G1 compared with G4, whereas the groups that were fed vitamin C with potassium nitrate showed a mild decrease compared with group potassium nitrate that had been fed potassium nitrate alone (G1). In conclusion, the feeding rabbits with potassium nitrate caused an increase in cholesterol, triglyceride and blood urea concentration in the serum, whereas the vitamin C ameliorates this effect.